The Prevalence of Binocular Vision Anomalies and Refractive Error among Secondary School Children in Southern Trinidad and Tobago. - Dr Ngozika Ezinne; Mohansingh, Safiyya; Rattan, Vishal (Faculty of Medical Sciences, The UWI, St. Augustine Campus, Trinidad and Tobago, 2023)
This research seeks to investigate the prevalence of Binocular Vision Anomalies and Refractive Error among Secondary School Students in Trinidad and Tobago. Methods: A cross sectional school-based study was done by conducting vision screenings in two different schools in south Trinidad to investigate the prevalence of BVA and refractive error. A website called picker wheel was used to select schools to be included. Information on demography was obtained, and refractive error and binocular vision testing were conducted. The data collected was entered into Microsoft excel and exported to Statistical Package for Social Sciences (SPSS). Pearson Chi Squared was used to describe the distribution of categorical values and association between variables were evaluated using Spearman’s rho using a p-value of <0.05 as the threshold for statistical significance. Results: A total of 95 students comprising of 49 (51.6%) males and 46 females (48.4%) ages 12-18 years participated in this study. The prevalence of BVA was 13.7% (13 children) with convergence insufficiency (6.2%) being the most prevalent type found. Refractive error was more prevalent accounting for 64.7% of participants, with myopia being the most prevalent (54.2%) type of refractive error. It was determined using the Spearman rho test that there is no statistically significant correlation between BVA and refractive error. Conclusion: The prevalence of BVA and refractive error among secondary school students in south Trinidad was found to be 13.7% and 64.7% respectively.